The prevalence of hypertension and its associated risk factors among older adults in Ghana - Dai, Baozhen; Addai-Dansoh, Stephen; Nutakor, Jonathan Aseye; Osei-Kwakye, Jeremiah; Larnyo, Ebenezer; Oppong, Stephen; Boahemaa, Priscilla Yeboah; Arboh, Francisca (Frontiers in Cardiovascular Medicine, 2022)
Background Hypertension is a worldwide health issue that primarily affects the elderly in our society. However, in comparison to the developed world, the prevalence of hypertension is higher in Sub-Saharan Africa. Objective This paper examines the prevalence of hypertension and its associated risk factors among older adults in Ghana. Methods Using the World Health Organization’s study on global AGEing and adult health (WHO SAGE) Wave 1 cross-sectional data collected via in-person structured interviews; paper and pencil interviews (PAPI) from ten administrative regions of Ghana using stratified multistage cluster design from respondents aged 50+ grouped by decade, this study analyzed a nationally representative sub-sample of 3,997 respondents employing binary logistic regression. Odds ratios (OR) and 95% confidence intervals (95% CI) were used to estimate risk factors associated with hypertension (blood pressure ≥ 130/80 mm/Hg). Results There was a 53.72% hypertension prevalence rate among older adults. Hypertension prevalence tends to increase with increasing age. The prevalence of hypertension was associated with residency (B = −0.18, OR = 0.84, p < 0.017), with urban residents being more at risk of hypertension than rural residents. The prevalence of hypertension increased with overweight (B = 0.66, OR = 1.94, p < 0.001) and obesity (B = 0.82, OR = 2.28, p < 0.001). The amount of fruit and vegetable intake was insignificant but had an inverse relationship with hypertension prevalence. Conclusion This study has shown that demographic and lifestyle factors significantly affect and explain the hypertension risk among older adults. Medical factors, such as chronic diseases, were largely insignificant and accounted for less hypertension prevalence. Therefore, when interpreting test findings in clinical practice, such as hypertension, it is essential to consider demographic and lifestyle factors. In addition, health policies and primary interventions that seek to improve the standard of living, lifestyle, and wellbeing of older adults need to be critically considered moving forward to lower hypertension prevalence among older adults in Ghana.